Factors affecting micro-barriers that hinder the development of Vietnamese private enterprises - Cong, Phan The (The journal of contemporary issues in business and government, 2021)
In line with Vietnam’s economic reform and development, small and medium-sized enterprises or Vietnamese private enterprises (SMEs) have experiencedphenomenonal growth. Despite this impressive achievement, Vietnam’s SMEs remain weak in terms of internal and external networking, competitiveness, innovativeness, human resource, and readiness to globalization. Theyhave actually encounteredseveral barriers in their development at both micro and macro levels in fact. Inquires of these barriers is meaningful in making policy recommendations to remove barriers to private enterprise development in countries where the State/Government is considered a major actor. This study focuses on evaluating factors affecting the micro-barrier system that hinder the development of private enterprises in Vietnam to answer two research questions:which factors influence micro-barriers that hinder the development of private enterprises in Vietnam and what is the degree of influence of those factors? The study applies quantitative research methods to measure the impact of factors on the micro-barriers system that hinder private enterprise development based on the survey sample of 392 private enterprises in Vietnam, which are mainly small and medium-sized private enterprises (most affected by micro barriers). Research findings indicate that state management policies; legal and tax systems, expanding scientific research and technological innovation activities are the main factors affecting the micro barriers that hinder the development of private enterprises in Vietnam. These results could become the experiences for other countries like Vietnam.